KEAMANAN DAN PENYISIPAN PESAN TEKS PADA GAMBAR DENGAN KRIPTOGRAFI METODE HILL CIPHER DAN STEGANOGRAFI METODE END of FILE - Miming Mardianti; Sutardi Sutardi; LM. Fid Aksara (Informatics Engineering Department of Halu Oleo University, 2019)
The security and confidentiality of data are one of the aspects that are very important in information systems at this time. Rapidly development of science and technology allows the emergence of new techniques, which can be misused by certain parties that threaten the security of information systems. The existence of these things needs to be applied to data security techniques to anticipate threats such as techniques of cryptography and steganography. This study combines two techniques securing data i.e. cryptography Hill Cipher (HC) method and steganography End of File (EoF) method. The results obtained from a combination of methods HC and EoF were successfully implemented in the process of encryption and decryption text messages which will then be inserted into the picture. The message was successfully inserted and extracted back on all sample images either by formatting *.jpg and *.png as well as at a resolution of 256x256 pixels and 512x512 pixels. Based on the results of the test image using MSE and PSNR resulting image quality is not good because the average value of the MSE obtained high 11263.113 and the value of average PSNR low 15.299 dB good image resolution 256 x 256 pixels and 512x512 pixels.Keywords—End of File, Hill Cipher, Cryptography, SteganographyDOI : 10.5281/zenodo.3255127